2022
DOI: 10.3390/su14074013
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Multisensory Interaction between Luminous, Thermal and Auditory Environments through the Spatial Promenade Experience: A Case Study of a University Campus in an Oasis Settlement

Abstract: This paper aimed to develop a multisensory approach in a university campus, based on quantitative and qualitative approaches, investigating sense walk experiences (thermo-visual sound walk) under interactions of luminous, thermal, and auditory environments. The study was conducted in October 2021, in Chetma university campus in Biskra city, southern Algeria, which remains a famous oasis settlement of arid regions over the country. A comparative and correlation analysis was performed between the physical dimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…The authors are aware that subjective measurements have important potential in the soundscape evaluation, 73 in parallel with measurements of the different physical dimensions of the acoustic environment. 74 , 75 Therefore, future research should focus on the subjective and objective investigation of long-term soundscape evaluation to preserve and improve the cultural soundscapes of different urban spaces in Algeria, taking into account, as a lesson, the negative effects of COVID-19 on the environment and public health in general, and its effect on substantial cultural, political and urban design changes, especially that COVID-19 will not be the last virus that will strike our cities. 76 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors are aware that subjective measurements have important potential in the soundscape evaluation, 73 in parallel with measurements of the different physical dimensions of the acoustic environment. 74 , 75 Therefore, future research should focus on the subjective and objective investigation of long-term soundscape evaluation to preserve and improve the cultural soundscapes of different urban spaces in Algeria, taking into account, as a lesson, the negative effects of COVID-19 on the environment and public health in general, and its effect on substantial cultural, political and urban design changes, especially that COVID-19 will not be the last virus that will strike our cities. 76 …”
Section: Discussionmentioning
confidence: 99%
“…This translation may be useful for the future studies of the researchers who are engaged in the translation of the soundscape attributes such as the international network of soundscape researchers constituting from different regions of the world which were established under the name of "Soundscape Attributes Translation Project" (SATP) and started its activity by the first group of collaborators in 2019 in a first stage with the expertise by a considerable geographical distribution, covering 15 different languages, 71 where the attributes translated by the SATP group was carried out mainly based on the study of the soundscape attributes identified by Axelsson et al 72 The authors are aware that subjective measurements have important potential in the soundscape evaluation, 73 in parallel with measurements of the different physical dimensions of the acoustic environment. 74,75 Therefore, future research should focus on the subjective and objective investigation of long-term soundscape evaluation to preserve and improve the cultural soundscapes of different urban spaces in Algeria, taking into account, as a lesson, the negative effects of COVID-19 on the environment and public health in general, and its effect on substantial cultural, political and urban design changes, especially that COVID-19 will not be the last virus that will strike our cities. 76…”
Section: Implication On Practice and Future Researchmentioning
confidence: 99%
“…Meanwhile, the physical characteristics are measured and verified using objective data measurement methods. For instance, Berkouk et al [27] conducted a sensory walking experiment at Chetema University's campus, comparing and correlating the walking experience data of three different routes (outdoor, semi-outdoor, and indoor). They specifically examined the effects of light, heat, and auditory environments on the walking experience.…”
Section: Introductionmentioning
confidence: 99%
“…The physical environment is a complex of many factors that represent the space's ambience, as a combination of multiple perceptions such as visual, thermal, audible, and olfactory perceptions offered by a physical environment for persons at a given time [10]. So, the landscape and the soundscape of an urban park significantly impact users' wellbeing.…”
Section: Introductionmentioning
confidence: 99%